Dermatology: how to manage atopic dermatitis in patients with skin of colour - Muskaan Sachdeva; Marissa Joseph (BioExcel Publishing Ltd, 2022)
Atopic dermatitis (AD) is a chronic inflammatory cutaneous disease prevalent in all skin types but can differ in pathogenesis and clinical presentation. It has been documented in the literature that AD is more prevalent in Asian and Black individuals than in white individuals. Genetic variations as well as cultural and socioeconomic factors have important implications for susceptibility to AD and response to treatment in skin of colour. In this narrative review, we discuss differences in the epidemiology, pathophysiology, clinical presentation and treatment of AD in skin of colour. Additionally, we highlight the need for greater inclusivity of non-white ethnic groups in clinical trials to develop targeted treatments for diverse populations. Moreover, awareness of differences in AD presentation amongst non-white individuals may encourage patients to seek medical care earlier, leading to timely management and improved outcomes.